GEOGRAPHICAL STUDY OF IRRIGATION FACILITIES IN MORADABAD DISTRICT - Singh, Mukesh; Kumar, Pradeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Irrigation is the main non-physical element of agriculture which helps in agricultural production in two ways. First, by increasing the yield per hectare and second, by increasing the area under multi-cropping. Moradabad district is situated between 28 degrees 06’ north latitude and 28 degrees 40’ and 78 degrees 04’ and 78 degrees 27’ east longitude. The total area is 2208 square kilometers. The total population is 31.26 lakh people and the density is 1415 people per square kilometer. In the study area, the net irrigated area is 168.93 thousand hectares, the area irrigated more than once is 172.95 thousand hectares and the gross irrigated area is 341.88 thousand hectares. The irrigation facilities include 511 kilometers of canals, 524 government tube wells, 3079 private tube wells, 91514 diesel-operated pumping sets and 13367 other facilities. In Moradabad district, the total irrigated area is 168.93 thousand hectares, of which 10 percent is irrigated by canals, 60.98 percent by tube wells, 25.52 percent by diesel-powered pumping sets and 3.50 percent by other means. In view of the increase in irrigated land, there is a need to increase and improve the means of irrigation.